Characterization of amorphous carbon films by PECVD and plasma ion implantation: The role of fluorine and sulfur doping - de Oliveira Neto, Antonio M.; Schreiner, Wido H.; Justo, João F.; de Oliveira, Alexandre M.; Rangel, Elidiane C. [UNESP]; Durrant, Steven F. [UNESP] (Elsevier, 2019)
We carry an investigation on the structural and optical properties of amorphous carbon films, containing fluorine and sulfur in their composition, grown by plasma enhanced chemical vapor (PECVD) and plasma immersion ion implantation deposition (PIIID) techniques. The films were grown by a combination of acetylene, sulfur hexafluoride, and argon gases. The chemical and optical properties of the films, prepared with different gas concentrations and voltages on the substrate, are analyzed by X-ray photoelectron spectroscopy and Fourier-transform infrared absorption spectroscopy. The results indicate that the application of negative pulses in the lower electrode allows greater incorporation of fluorine atoms with a smaller amount of hexafluoride gas at the reactor feed. Additionally, sulfur incorporation has been detected in the films in concentrations up to 18%. The influence of the incorporation of fluorine and sulfur on the optical properties is also explored.